EFFORT TO INCREASE THE ROLE OF GUARDIANS AND PREGNANT WOMEN FOR CHILDREN'S HEALTH SCIENCE IN THE WOMB WITH RADIOLOGY SCREENING - Majdawati, Ana; Brahmana, Ivanna Beru; Yuliantini, Lisa Sophia (Universitas Muhammadiyah Mataram, 2025)
Abstract: Early detection of fetal health is an essential step in preventing complications that may affect a child's quality of life. Radiological screening, particularly ultrasonography (USG), serves as a tool to detect fetal health conditions. However, the understanding of student guardians and pregnant women regarding the urgency of radiological screening remains limited. This community service program aims to raise awareness and understanding among student guardians and pregnant women about the importance of radiological screening for the early detection of disorders that affect the growth and development of infants and toddlers. The activity was held on Friday, February 28, 2025, from 08:00 to 10:00 at one early childhood education (PAUD) partner in Sleman. Methods included lectures, interactive discussions, and the formation of 10 PAUD health cadres from the partner institution. The follow-up to this program involved training the cadets on preventive efforts using flipcharts that outlined the necessary actions for pregnant women and parents to monitor the growth and development of infants and toddlers, along with practical sessions in the community and with students at PAUD . The pre-test score was 63.28, while the post-test score increased to 82.68, indicating improved knowledge. In conclusion, this community service activity enhanced the knowledge of cadres and student guardians regarding the importance of radiological examinations (ultrasound and bone age assessments) for the early detection of growth and development in infants and toddlers, starting from the prenatal stage.